Assessment of antidiabetic potential and phytochemical profiling of Rhazya stricta root extracts - Rashid Mahmood; Waqas Khan Kayani; Tanveer Ahmed; Farnaz Malik; Shahzad Hussain; Muhammad Ashfaq; Hussain Ali; Samina Rubnawaz; Brian D. Green; Danielle Calderwood; Owen Kenny; Gerardo A. Rivera; et al. (BMC, 2020)
Abstract Background Diabetes mellitus is a chronic disease characterized by hyperglycemia that may occur due to genetic, environmental or lifestyle factors. Natural remedies have been used to treat diabetes since long and many antidiabetic compounds of varied efficacies have been isolated from medicinal plants. Rhazya stricta has been used for decades for the treatment of diabetes mellitus and associated ailments. Considering the folkloric use of R. stricta against diabetes, it was aimed to investigate the effectiveness of its root extracts against diabetes through in vitro assays and in vivo studies using animal model along with phytochemical profiling through GCMS. Methods Various fractions of Rhazya stricta obtained through column chromatography were evaluated for a variety of assays including α-glucosidase, Dipeptidyl peptidase-IV (DPP-IV), β-secretase and Glucagon-like peptide-1 (GLP-1) secretion studies. For the in vivo studies the alloxan-induced diabetic mice were treated with root extracts and blood glucose levels, HbA1C, and other biochemical markers along with the histological study of the liver were done. The phytochemical identification was performed using an Agilent 7890B GC coupled to a 7010 Triple Quadrupole (MS/MS) system. GraphPad Prism software version 5.01 was used for statistical analysis. Results Majority of the extract fractions showed excellent results against diabetes by inhibiting enzymes DPP-IV (Up to 61%) and β-secretase (Up to 83%) with IC50s 979 μg/ml and 169 μg/ml respectively with increase in the GLP1 secretion. The results of in vivo studies indicated a marked reduction in blood glucose and HbA1c levels along with positive effects on other parameters like lipid profile, liver functions and renal functions of extract-treated mice as compared to control. The histological examination of the liver demonstrated hepatoprotective effects against diabetes led changes and various classes of phytochemicals were also identified through GCMS in different fractions. Conclusion The results revealed strong antidiabetic activity of R. stricta root with the potential to protect body organs against diabetic changes. Moreover, a variety of phytochemicals has also been identified through GCMS that might be responsible for the antidiabetic potential of Rhazya stricta root. Graphical abstract